2007
DOI: 10.1038/emm.2007.56
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of p31comet gene, a negative regulator of Mad2, in human hepatocellular carcinoma

Abstract: Failure of mitotic checkpoint machinery leads to the chromosomal missegregation and nuclear endoreduplication, thereby driving the emergence of aneuploidy and tetraploidy population. Although abnormal nuclear ploidy and the resulting impairment of mitotic checkpoint function are typical physiological event leading to human hepatocellular carcinoma, any mutational change of mitotic checkpoint regulators has not yet been discovered. Therefore, we investigated the mutation of p31 comet , a recently identified mit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Therefore, our clinicopathological assessment of UbcH10 is compatible with prior epigenetic and biological studies that have implicated UbcH10 as a predictor of the biological characteristics of cancer. Furthermore, lower levels of p31comet, another molecule that induces the metaphase to anaphase transition, also acts as a potential prognostic marker in cancer [34,35]. Moreover, Usp44 inhibits Cdc20 degradation and counteracts UbcH10 to decelerate the metaphase to anaphase transition [36].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our clinicopathological assessment of UbcH10 is compatible with prior epigenetic and biological studies that have implicated UbcH10 as a predictor of the biological characteristics of cancer. Furthermore, lower levels of p31comet, another molecule that induces the metaphase to anaphase transition, also acts as a potential prognostic marker in cancer [34,35]. Moreover, Usp44 inhibits Cdc20 degradation and counteracts UbcH10 to decelerate the metaphase to anaphase transition [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous reports showing a lower level of p31 comet, another molecule that prevents premature anaphase-to-metaphase transition and acts as a potential prognostic marker in cancer, may support our present findings. (39,40) The current opinion that a balance between the anaphasemetaphase promoters UbcH10 or p31comet and suppressor Usp44 could determine the accurate chromatid separation, further explains the significance of UbcH10 in patients with breast cancer. (41) The regulatory role of UbcH10 in tumorigenesis is consistent with the current paradigm.…”
Section: Clinicopathological Analysis Confirms the Oncogenic Role Ofmentioning
confidence: 99%
“…As for MAD2L1, Li et al (30) identified this gene as a vital mediator of pathways underlying chromosomal regulation in HCC. Yun et al (31) demonstrated that inhibition of MAD2L1 expression led to the suppression of HCC cell proliferation, migration and invasion, suggesting that MAD2L1 may serve as a potential target for the clinical treatment and prognostic evaluation of patients with HCC. In agreement with a previous study (32), TOP2A may be a valuable prognostic marker and predictor of poor survival in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%